Ethnicity, gender and risky sexual behaviour among Nigerian youth: an alternative explanation. Issue 1 (December 2017) - Odimegwu, Clifford; Somefun, Oluwaseyi
Abstract Background While studies in demography and public health have acknowledged the role of ethnic differences, the influence of ethnicity on youth sexual behaviour in Nigeria has received little or no attention. It is important to know how cultural norms and gender roles, which vary by ethnicity, may promote or prevent risky behaviour. Such information could provide insights into previously undetected sexual behaviour in multi-ethnic situations. Methods The Nigeria Demographic and Health Surveys (NDHS) for 2003, 2008 and 2013 were pooled to examine the relationship between ethnicity and youth sexual reproductive health, proxied by age at sexual debut, multiple sexual partners (MSP) and condom use at last sexual activity, among the 6304 females and 1549 males who reported being sexually active in the four weeks preceding the survey. Multivariate analysis using a Cox proportional hazard regression model was used to determine the risk factors for early sexual activity among young people (15–24). Logistic regression was used to predict condom use at last sexual activity and MSP. Results The median age at first sexual activity was 16 for females and 17 for males. 43% of male youths used condoms in their last sexual activity, compared to only 16% among females and a higher number of males (81%) had multiple sexual partners compared to females (35%). For females, elevated risks of first sex was higher among Hausa/Fulanis aged 15–19 and elevated risk of first sex was higher among Yoruba males. Conclusion This study provides further evidence that in order to promote protective sexual behaviours among youth in Nigeria, social, cultural and gender-specific tactics should be put in place for the prevention of HIV and other STIs.